A mixed-methods study on negative psychological states of infertile women undergoing assisted reproductive treatment - Jia-Yu Hu; Yi-Dan Wu; Zhen Xiao; Meng-Ting Yu; Yue-Feng Liu; Yu-Ting Peng; Xiao-Hua Fu; Yu Zhang (Scientific Reports)
Abstract The incidence of infertility in the world is gradually increasing, and assisted reproductive treatment is one of the main methods for infertility treatment worldwide. Infertile women undergoing assisted reproductive treatment are likely to have a negative psychological state. However, deficits in the existing knowledge about women’s negative psychological conditions greatly limit the implementation and effectiveness of psychological interventions. The aim of this study was to identify the specific risk factors for a negative psychological state in infertile women undergoing assisted reproductive treatment. A mixed-methods design that combined quantitative survey and qualitative interview was adopted in this study. In the quantitative study, the DASS-21 questionnaire was administered on 437 infertile women undergoing assisted reproductive treatment to evaluate the prevalence of negative psychological symptoms. Descriptive statistics were conducted on the participants’ demographic information and clinical data, and multiple linear regression analysis was performed on the quantitative data to determine the risk factors for negative psychological states. In the qualitative study, semistructured interviews were conducted with 14 women who reported negative psychological symptoms in the quantitative survey. Thematic analysis was employed for qualitative data. The results of quantitative and qualitative study were comprehensively analyzed and classified. The results of the quantitative survey suggested a high prevalence of anxiety (24.3%), depression (10.8%) and stress (8.7%). Univariate analysis revealed that a negative psychological state in infertile women is significantly related to occupation type, household income, infertility factors, duration of infertility treatment, and the number of previous assisted reproductive treatment cycles (P < 0.05). Multivariate linear regression analysis indicated that annual per capita household income was the primary factor influencing depression scores (P < 0.05), the duration of infertility treatment and occupation type were the primary factors influencing anxiety scores (P < 0.05), unexplained infertility was the primary factor influencing stress scores (P < 0.05). Subsequent qualitative research provided a more detailed exploration of the characteristics and sources of negative psychological states of infertile women, which yielded five key themes: characteristics of a negative psychological state, medical aspects, family issues, conflicts with normal life, and social context influences. The prevalence of a negative psychological state is high among infertile Chinese women undergoing assisted reproductive treatment. The results of mixed-methods study reveal that medical factors associated with assisted reproductive treatment, insufficient family emotional support, conflicts between work and treatment, and financial burdens are the main causes of negative psychological states. Future research needs to explore more effective psychological intervention methods to improve the psychological state of infertile women.